2017
DOI: 10.3390/computation5010008
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Computational Analysis of a New Vertical Axis Wind Turbine, Named KIONAS

Abstract: This paper concentrates on a new configuration for a wind turbine, named KIONAS. The main purpose is to determine the performance and aerodynamic behavior of KIONAS, which is a vertical axis wind turbine with a stator over the rotor and a special feature in that it can consist of several stages. Notably, the stator is shaped in such a way that it increases the velocity of the air impacting the rotor blades. Moreover, each stage's performance can be increased with the increase of the total number of stages. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…They comparedthe coefficient of lift to drag ratio to find the better aerofoil amongst the two. Douvi C. Eleni, Tsavalos I. Athanasios and Margaris P. Dionissios [2] researched on the better turbulence model for NACA 0012 aerofoil CFD analysis amongst the three turbulence models namely Spalart-Allmaras, Realizable k-έ and k-ε and k-ω shear stress transport (SST). The research concluded as k-ω SST two equation model gives more practical results than the other two.…”
Section: Necessity Of Analysismentioning
confidence: 99%
“…They comparedthe coefficient of lift to drag ratio to find the better aerofoil amongst the two. Douvi C. Eleni, Tsavalos I. Athanasios and Margaris P. Dionissios [2] researched on the better turbulence model for NACA 0012 aerofoil CFD analysis amongst the three turbulence models namely Spalart-Allmaras, Realizable k-έ and k-ε and k-ω shear stress transport (SST). The research concluded as k-ω SST two equation model gives more practical results than the other two.…”
Section: Necessity Of Analysismentioning
confidence: 99%